Notes on the Evolution of Compulsory Conciliation in Canada / Notes sur l'évolution de la conciliation obligatoire au Canada - Williams, C. Brian (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1964)
SummaryThe purpose of this paper is to review the historical evolution of the concept of compulsory conciliation in federal labor law, and to suggest some four features in its history which appear to have been overlooked in the literature on the subject.